SUBSTANTIATION OF THE CONCEPT OF TECHNICAL AND PHYSICAL TRAINING OF SWIMMERS IN A LONG-TERM TRAINING CYCLE - Arishin, A.V.; Pogrebnoy, A.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to scientifically substantiate the concept of technical and physical training of swimmers in a long-term training cycle. Methods and structure of the study. To solve the tasks, we used the material obtained as a result of many years of research of 607 swimmers at the training stage (three years), the stage of improving sportsmanship (three years) and higher sportsmanship (two years), questioning 49 coaches of sports teams. Biomechanical (computer video analysis, analysis of intracycle swimming speed, analysis of dynamic parameters), pedagogical (physical fitness testing), physiological (blood lactate) methods were used in the work. Results and conclusions. Synergistically coupled training means and additional methods of physical and technical training based on the achievement of a systemic effect (emergence) have been developed. Based on the identification of significant parameters of physical and technical readiness, which have a high specificity, a variant of constructing the training activity of swimmers was found, in which physical and technical training are combined into one integrative system - technical and physical training. Thus, the allocation of technical and physical training as a single part of the training process due to the achievement of a synergistic systemic effect (emergence) allows us to determine a new direction in the planning, systematization and management of sports training components, which contributes to the achievement of higher sports results.